Recent Developments of Nanomaterials in Crop Growth and Production: The Case of the Tomato (Solanum lycopersicum) - Eric G. Echeverría-Pérez; Vianii Cruz-López; Rosario Herrera-Rivera; Mario J. Romellón-Cerino; Jesusita Rosas-Diaz; Heriberto Cruz-Martínez (Agronomy)
Tomatoes are a fundamental part of the daily diet, rich in carbohydrates, vitamins, minerals, carotenoids, and polyphenols. Nonetheless, optimal fruit yield and quality typically depend on the application of synthetic agrochemicals. However, the irrational use of these agrochemicals has caused various environmental problems. Therefore, it is necessary to develop alternatives to conventional agrochemical products. Applying nanomaterials as fertilizers in tomato production is emerging as a promising approach, with documented improvements in germination, vegetative development, and fruit yield. Therefore, we present a comprehensive review of recent developments (2015–2024) in the application of nanomaterials in tomato crops, with a particular emphasis on the significance of nanomaterial characteristics in their role as fertilizers. Several types of nanomaterials, such as ZnO, Ag, TiO2, Si, hydroxyapatite, P, Zn, Se, CuO, Cu, Fe, Fe2O3, CaO, CaCO3, and S, have been evaluated as fertilizers for tomato crops, with ZnO nanoparticles being the most extensively studied. However, it is pertinent to conduct further research on the less-explored nanomaterials to gain a deeper understanding of their effects on seed germination, plant growth, and fruit quality and quantity.